Comprehensive kinetic study on ammonia/ethylene counter-flow diffusion flames: influences of diluents - Zhimei Shu; Tingting Xu; Jiayi Xiao; Qige Deng; Xuan Zhao; Tianjiao Li; Yaoyao Ying; Dong Liu (International Journal of Coal Science & Technology, 2024)
Abstract This study aimed to investigate the effects of ammonia addition on ethylene counter-flow diffusion flames with different diluents on the fuel or oxidizer side, using kinetic analyses. A special emphasis was put on assessing the coupled chemical effects of NH3 and CO2 on C2H4 combustion chemistry. The chemical effects could be evaluated by comparing fictitious inert NH3 or CO2 with normal active NH3 or CO2. The results revealed that the addition of NH3 decreased the mole fractions and production rates of key soot precursors, such as acetylene, propynyl, and benzene. When CO2 was used as the dilution gas, the coupled chemical effects of NH3 and CO2 were affected by the chemical effects of CO2 to varying degrees. With the oxidizer-side CO2 addition, the coupled chemical effects of NH3 and CO2 reduced the mole fractions of H, O, OH radicals, acetylene, propynyl, and benzene, while the effects differed from the fuel-side CO2 addition. The coupled chemical effects of NH3 and CO2 also promoted the formation of aldehyde contaminants, such as acetaldehyde, to some extent, particularly with CO2 addition on the oxidizer side.